050 Introduction of a quality of trauma care patient reported experience measure during weekly trauma governance review meetings. Issue 12 (21st November 2019) - Owen, Matthew; Graham, Blair; Smith, Jason
Abstract : The 2005 Darzi Report stated that Patient Safety, Clinical Effectiveness and Patient Experience should be afforded parity when evaluating services. Positive Patient Experience (PEx) is correlated with improved outcomes across a wide range of conditions. In our hospital, we conduct weekly governance review of trauma cases, but no PEx element was previously included. This pilot study has the primary aim of evaluating PEx and incorporating this into weekly trauma meetings, specifically identifying strengths and vulnerabilities in service provision. A secondary aim was to stimulate improvement of the trauma system based on feedback received. The setting for this pilot study was the Peninsula Trauma Network Major Trauma Centre at University Hospitals Plymouth NHS Trust. The 13-item validated Short Form Quality of Trauma Care Patient Reported Experience Measure (SF-QTACPREM), originally developed by Bobrovitz et al, was directly administered to trauma patients able to provide informed consent from November 2018 onwards. Items are equally weighted. A positive response is assigned 7.69%, a neutral response 3.85% and a negative response, 0%. By consensus, a target overall PEx score of >90% has been determined. PEx data have been successfully incorporated into trauma meetings. Data are presented in meetings via a visual dashboard (figure 1 ). Cumulative data are compiled into an aggregate PEx data slide (figure 2 ). Current mean average PEx Score (n=30) is 81.79% (Range 46.15%–100%). Aggregate data reveal that communication domains tend to score lower whereas technical domains involving medical care score more highly. Provision of mental health support following injury has been identified as a priority area for improvement. As a direct result of negative reported experience or a low PEx score, specialist trauma nurses return to address patient concerns, increasing service responsiveness in real-time. In the future, it is hoped that this pilot will be expanded to include all network trauma patients.